2018
DOI: 10.1007/s40430-018-1482-0
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of activation energy and binary chemical reaction for 3D flow of Cross-nanofluid with radiative heat transfer

Abstract: In view of ecological concern and energy security, execution of refrigeration system should be enriched which can be done by improving the characteristics of working liquids. The nanoliquids have gained interest in industrial and engineering fields due to their outstanding thermophysical features. Researchers used nanoliquids as working liquid and detected substantial variations in thermal performance. In the present research work, our intention is to explore the impact of nonlinear thermal radiation and varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…He analyzed the influences of entropy and exergy on the presented model and reported that entropy loss enhanced in attendance of stronger magnetic field. Khan et al [ 24 ] examined the numerical solution of 3D cross nanofluid with activation energy and binary chemical reaction with zero mass flux and convective boundary conditions. They noticed that higher estimates of activation energy boosted the concentration of the cross nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…He analyzed the influences of entropy and exergy on the presented model and reported that entropy loss enhanced in attendance of stronger magnetic field. Khan et al [ 24 ] examined the numerical solution of 3D cross nanofluid with activation energy and binary chemical reaction with zero mass flux and convective boundary conditions. They noticed that higher estimates of activation energy boosted the concentration of the cross nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…In the same direction, Kameswaran et al showed the effect of viscous dissipation in nanofluid flow over a stretching sheet. The combined effect of the radiation and viscous dissipation has been discussed by Makanda et al, Khan et al, and Irfan et al…”
Section: Introductionmentioning
confidence: 98%
“…In the same direction, Kameswaran et al 32 showed the effect of viscous dissipation in nanofluid flow over a stretching sheet. The combined effect of the radiation and viscous dissipation has been discussed by Makanda et al, 33 Khan et al, 34 and Irfan et al 35 This study focused on the investigation of linear radiation and viscous dissipation on the fluid flow about a vertical cone/wedge/vertical plate implanted in a nanofluid-saturated non-Darcy porous medium. The system of nonlinear partial differential equations is solved using a local linearization technique.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies about activation energy in fluid dynamics. Consequently, Khan et al 21 have measured the activation energy of 3D cross‐nanofluid flow with capricious thermal conductivity, nonlinear thermal radiation with chemical processes, and heat sink/source. Sajid et al 22 also examined the incorporation analysis of heat and mass transfer with activation energy, variable thermal conductivity, and nonlinear thermal radiation for Darcy‐Forchheimer flow of a Maxwell nanofluid over a linearly stretching surface.…”
Section: Introductionmentioning
confidence: 99%